2021
DOI: 10.1002/jbm.b.34975
|View full text |Cite
|
Sign up to set email alerts
|

Thermal changes during drilling in human femur by rotary ultrasonic bone drilling machine: A histologic and ultrastructural study

Abstract: Undue heat production in surgical bone drilling leads to osteonecrosis and can be an important cause of failure of osteosynthesis, impaired healing, and loosening of implants following orthopedic surgery. The present work aims to minimize heat production below the critical temperature for thermal osteonecrosis (i.e., 47°C) and obviate thermal bone damage due to drilling. A total of 20 samples from the shaft of the human femur were obtained at autopsies and drilling was performed at room temperature by an opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It is crucial to emphasize the significance of reliable bone surgeries, especially in robot-assisted procedures [16][17][18][19][20]. This research highlights the potential of the proposed model in achieving precise temperature control during bone drilling, which could significantly contribute to the success and safety of such surgical interventions.…”
Section: Optimization Of Process Temperature In Bone Drillingmentioning
confidence: 90%
“…It is crucial to emphasize the significance of reliable bone surgeries, especially in robot-assisted procedures [16][17][18][19][20]. This research highlights the potential of the proposed model in achieving precise temperature control during bone drilling, which could significantly contribute to the success and safety of such surgical interventions.…”
Section: Optimization Of Process Temperature In Bone Drillingmentioning
confidence: 90%
“…Some studies found a lower cutting force and an elevated temperature when vibrational plane cutting and orthogonal elliptical vibration-assisted cutting were used in bones 32 , 33 . Some recent studies evaluated the performance of UAD with regard to biological damage induced in the bone 34 . Drilling assisted by vibrations imposed on the drill was also found helpful for maintaining structural integrity of the bone 35 .…”
Section: Introductionmentioning
confidence: 99%